2020
DOI: 10.1177/1073274820944286
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a Highly Sensitive qPCR Assay for the Detection of Plasma Cell-Free Epstein-Barr Virus DNA in Nasopharyngeal Carcinoma Diagnosis

Abstract: Quantification of plasma cell-free Epstein Barr virus DNA (cf EBV DNA) has been suggested as a promising liquid biopsy assay for screening and early detection of nasopharyngeal carcinoma (NPC). However, the diagnostic value of this assay is currently not known in the population of Vietnam, one of the countries which contributed the most to the NPC cases. Herein, we have reported a highly sensitive quantitative polymerase chain reaction (qPCR)-based assay targeting cf EBV DNA for the detection of NPC. A standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…17 Moreover, previous studies have indicated that the detection of plasma cell-free EBV DNA could serve as a diagnostic biomarker of NPC. 18,19 However, due to the instability and hysteresis of the detection of EBV, finding a novel biomarker to improve the efficiency and accuracy is still necessary for patient diagnosis. a noninvasive diagnostic tool and numerous studies have reported the diagnostic capacity of total RNA in the serum or plasma of patients for NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, previous studies have indicated that the detection of plasma cell-free EBV DNA could serve as a diagnostic biomarker of NPC. 18,19 However, due to the instability and hysteresis of the detection of EBV, finding a novel biomarker to improve the efficiency and accuracy is still necessary for patient diagnosis. a noninvasive diagnostic tool and numerous studies have reported the diagnostic capacity of total RNA in the serum or plasma of patients for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Some different types of circulating sEVs have been identified in NPC, including EBV‐related sEVs and pure NPC‐derived sEVs 17 . Moreover, previous studies have indicated that the detection of plasma cell‐free EBV DNA could serve as a diagnostic biomarker of NPC 18,19 . However, due to the instability and hysteresis of the detection of EBV, finding a novel biomarker to improve the efficiency and accuracy is still necessary for patient diagnosis 3 .…”
Section: Discussionmentioning
confidence: 99%